Penatalaksanaan Kompres Dingin Terhadap Intensitas Nyeri Pada Asuhan Keperawatan Tonsilitis Kronis Dengan Tonsilektomi - Sari Octarina Piko; Tuti Elyta; Nurul Karomah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Tonsillectomy is defined as a surgical procedure to completely remove the tonsils, including their capsules by dissection of the peritonsillar space between the tonsil capsule and the muscular wall. Purpose: This scientific paper is to provide an overview of the Management of Cold Compresses on Pain Intensity in Nursing Care of Chronic Tonsillitis with Tonsillectomy. Methods: The design of this research is descriptive analytic with case study method. The non-pharmacological implementation of Post Tonsillectomy is the Administration of Cold Compresses to Pain Intensity carried out at Bhayangkara M.Hasan Hospital Palembang from 08 May 2023 to 10 May 2023 and 16 May 2023 to 19 May 2023. The subjects of this study were 2 post tonsillectomy patients. Results: After giving cold compresses for 3 days, both patients experienced a decrease in pain scale. Pain scale Mr 'T' before giving cold compresses pain scale 4 after giving cold compresses pain scale 0. Meanwhile, pain scale Nn 'S' before giving cold compresses pain scale 5 after giving cold compresses pain scale 1. Conclusion: After Cold Compress was given to Post Tonsillectomy patients for 3 days, both patients experienced a decrease in pain scale. The intervention was successful.